Case report: Multisystem inflammatory syndrome in children associated with COVID-19, macrophage activation syndrome, and incomplete Kawasaki disease - Martínez-García, Jesús Javier; López-Acosta, Jesús Ramon; Arce-Cabrera, Daniela; León-Sicairos, Nidia; Hernández-Parra, Ana Cristina; Cuen-Diaz, Hector Melesio; Zatarain-Lopez, Ricardo; Canizalez-Roman, Adrian (Frontiers in Pediatrics, 2023)
Background: Multisystem inflammatory syndrome in children (MIS-C), is a severe complication of coronavirus disease 2019 (COVID-19), characterized by persistent fever, systemic inflammatory response, organ failure. MIS-C with a history of COVID-19, may share clinical features with other well-defined syndromes such as macrophage activation syndrome, Kawasaki disease, hemophagocytic syndrome and toxic shock syndrome. Case 1. 11-year-old male with a history of hypothyroidism and precocious puberty with positive antibody test for COVID-19. He was admitted for fever, poor general condition, severe respiratory distress, refractory shock and multiple organ failure. Laboratory with elevated inflammatory parameters, bone marrow aspirate with hemophagocytosis. Case 2. A 13-year-old male with a history of attention deficit hyperactivity disorder and cognitive delay. He presented clinical manifestations of Kawasaki disease, fever, conjunctival congestion, exanthema and hyperemia in oral mucosa, tongue and genitals, with refractory shock and multiple organ failure. RT-PCR and negative antibodies for COVID-19, elevated inflammation parameters and bone marrow aspirate with hemophagocytosis. Patients required intensive care with invasive mechanical ventilation, vasopressor support, intravenous gamma globulin, systemic corticosteroids, low molecular weight heparin, antibiotics, monoclonal antibodies and, in patient 2, renal replacement therapy. Conclusions. Multisystemic Inflammatory Syndrome in Children can have atypical manifestations, identifying them early is very important for the timely treatment and prognosis of patients.